Significant differences in T cell receptor repertoires in lung adenocarcinomas with and without epidermal growth factor receptor mutations. Issue 3 (16th February 2019) - Miyauchi, Eisaku; Matsuda, Tatsuo; Kiyotani, Kazuma; Low, Siew‐Kee; Hsu, Yu‐Wen; Tsukita, Yoko; Ichinose, Masakazu; Sakurada, Akira; Okada, Yoshinori; Saito, Ryoko; Nakamura, Yusuke
Abstract : Recent clinical trials of non‐small cell lung cancer with immune checkpoint inhibitors revealed that patients with epidermal growth factor receptor ( EGFR ) mutations had more unfavorable outcomes compared with those with wild‐type EGFR . However, the underlying mechanism for the link between EGFR mutations and immune resistance remains unclear. We performed T cell receptor (TCR) repertoire analysis of resected lung adenocarcinoma tissues with and without EGFR mutations to investigate the characteristics of TCR repertoires. We collected a total of 39 paired (normal and tumor) lung tissue samples (20 had EGFR mutations) and conducted TCR repertoire analysis as well as whole‐exome sequencing (WES) and transcriptome analysis. The TCR diversity index in EGFR ‐mutant tumors was significantly higher than that in EGFR ‐wild‐type tumors (median [range] 552 [162‐1, 135] vs 230 [30‐764]; P <  .01), suggesting higher T cell clonal expansion in EGFR ‐wild‐type tumors than in EGFR ‐mutant tumors. In WES, EGFR ‐mutant tumors showed lower numbers of non‐synonymous mutations and predicted neoantigens than EGFR ‐wild‐type tumors ( P  <   .01, P  =   .03, respectively). The number of non‐synonymous mutations revealed a positive correlation with the sum of frequencies of the TCRβ clonotypes of 1% or higher in tumors ( r  =   .52, P  =   .04). The present study demonstrates significant differences in TCR repertoires and the number of predicted neoantigens between EGFR ‐mutant and wild‐type lung tumors. Our findings provide important information for understanding the molecular mechanism behind EGFR ‐mutant patients showing unfavorable responses to immune checkpoint inhibitors. Abstract : We report distinct characteristics of TCR repertoires in lung adenocarcinomas with and without EGFR mutations.